INTRODUKSI PENGOLAHAN YOGURT DRINK DARI SUSU KAMBING DAN SARI BUAH NANAS DI DESA SEPANG BUSUNG BIU BULELENG - Sujaya, I.N.; Nocianitri, K.A.; Fatmawati, N.N.D.; Utami, N.W.A.; Pratiwi, I.D.P.K.; Ramona, Y. (Buletin Udayana Mengabdi, 2022)
Goat milk is produced by Tunas Mekar Goat farmer grout located at Sepang Village, Busungbisu, Buleleng. This product is highly potent to improve the income of the local farmers. Nevertheless, the use of goat milk as raw material for foods products is still limited. This program aimed to find out possible utilization of goat milk produced by local farmers at Sepang Village for the production varies of food products. Goat odors are the main problem in goat milk-based food products especially goat milk set-yogurt. Thus, the production of drink yogurt with the addition of pineapple juice is a promising technology to overcome goat odors in goat milk yogurt. This program was undertaken through sequential steps such as knowledge building of the housewives (the target population in this program) followed by training in yogurt making, drink yogurt making as well as product packaging and labeling. All programs were performed well as indicated by the active involvement of the participants. Throughout this program, the goat milk farmers group and housewives are now capable to produce drink yogurt to improve the value-added of their local produce goat milk, which possibly increase their economic income.    Keywords: Goat milk, pineapple, Sepang, yogurt drink